Gone with the wind: Short- and long-term responses of leaf-cutting ants to the negative effect of wind on their foraging activity - Alma, Andrea Marina (2016)
The fitness and survival of organisms ultimately depend on their feeding. Therefore, foraging behaviors should be selected to maximize cost-benefit ratio. Wind may restrict and modify animal movements increasing the cost of foraging, especially when the animal carries resources that intercept wind. We quantified the effect of wind on the foraging of leaf-cutting ants and evaluated whether this effect varies with 1) leaf fragment traits, such as area, mass, and shape, and 2) the characteristics of the foraging trail system. We also tested whether these ants show a short-term response to wind by selecting loads with characteristics that reduce wind interception, and a long-term response, by arranging the spatial design of the trail system in a way that reduces that effect. We found that in windy conditions, the speed of loaded ants was reduced by 55%, and ants were blown off the trail 28 times more than in windless conditions. However, wind only affected ants walking along trails that were perpendicular to wind direction or parallel upwind. Wind effect increased with area, mass, and shape of loads. At the short term, ants reduced the negative effect of wind by selecting smaller, lighter, or more elongated loads. However, trails showed no particular spatial distribution in relation to wind direction. This is the first study that quantifies the negative consequences of wind on leaf-cutting ants' foraging and reports behaviors that can reduce this effect. Our work illustrates how short-term behavioral responses can mitigate the negative effect of an understudied environmental factor on ant foraging.